Role of the Receptor for Advanced Glycation End Products (RAGE) and Its Ligands in Inflammatory Responses - Kaylen Cross; Stefan W. Vetter; Yousuf Alam; Md. Zahidul Hasan; Anupom Deb Nath; Estelle Leclerc (Biomolecules)
Since its discovery in 1992, the receptor for advanced glycation end products (RAGE) has emerged as a key receptor in many pathological conditions, especially in inflammatory conditions. RAGE is expressed by most, if not all, immune cells and can be activated by many ligands. One characteristic of RAGE is that its ligands are structurally very diverse and belong to different classes of molecules, making RAGE a promiscuous receptor. Many of RAGE ligands are damaged associated molecular patterns (DAMPs) that are released by cells under inflammatory conditions. Although RAGE has been at the center of a lot of research in the past three decades, a clear understanding of the mechanisms of RAGE activation by its ligands is still missing. In this review, we summarize the current knowledge of the role of RAGE and its ligands in inflammation.